ANALISIS YURIDIS OUTSOURCING TERHADAP PERUSAHAAN DAN PEKERJA/BURUH - Naibaho, Rumintang; Sihotang, Maria Happy Claudia; Ghozali, Elizabeth (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The author's purpose in conducting research refers to understanding the comparison of the concept of outsourcing between Law No. 13 of 2003 concerning Manpower compared to the Job Creation Law No. 6 of 2023, writing this research is important to do in order to find out what things are allowed in the outsourcing system so as not to eliminate legal certainty. The author uses a normative research type that uses secondary data consisting of primary legal materials, namely laws and regulations, secondary legal materials, namely research results and tertiary legal materials obtained from encyclopedias and legal dictionaries, the data is then analyzed qualitatively and conclusions are drawn with deductive logic. In general, this study discusses how changes in the concept of outsourcing between Law No. 13 of 2003 concerning Manpower and the Job Creation Law No. 6 of 2023, different concepts will have different impacts on the practice of implementing the concept. The results of this author's research show that with a significant comparison of the concept of outsourcing in the 2023 Job Creation Law regarding the limitations of work implementation related to work agreements, it is contrary to the wishes of workers who are considered detrimental to workers, instead of providing legal certainty to workers, it actually opens up opportunities for companies to be able to outsource work sectors, such as those that are core businesses, and currently no longer use the separation between